Channel arrangements and depositional styles in the Sao Lourenco fluvial megafan, Brazilian Pantanal wetland - Assine, Mario Luis [UNESP]; Corradini, Fabricio Anibal; Pupim, Fabiano do Nascimento [UNESP]; McGlue, Michael Matthew (Elsevier B.V., 2014)
The Brazilian Pantanal is an extensive lowland tropical basin characterized by the presence of fluvial megafans and seasonally-inundated savanna floodplain wetlands. With an area of about 16,000 km(2), the Sao Lourenco is the second largest megafan in the Pantanal. Three distinct fluvial channel styles that formed at different times during the late Quaternary are found here. A geomorphological and sedimentary assessment of these depositional patterns provides valuable insight on the environmental context of their evolution. New optically stimulated luminescence data indicate that the upper five meters of sediment in the Sao Lourenco megafan has been accumulating since the late Pleistocene. Ancient fan lobes, located in upper and intermediate fan settings, consist of medium- and coarse-grained fluvial sands and exhibit well-preserved distributary braided paleochannels on their surfaces. As the megafan evolved through time, Pleistocene lobes were incised by a prominent valley filled with Holocene-aged meander belt deposits, which consist of silts interbedded with very fine sands and clays. Currently, the incised valley is a zone of sediment bypass. Modern deposition occurs along the distal toe of the megafan system, where lobes characterized by distributary channel-levee ridges are widespread. These features formed by progradation of avulsion belts into a broad swampy floodbasin, which caused the lower portion of the meander belt to be abandoned. The significant differences observed in intra-fan morphology appear to be linked to the variability in effective precipitation. Fan lobes deposited with braided distributary channels occurred under relatively dry conditions in the late Pleistocene. By contrast, aggradational meander belt deposits and lobes with distributary channel-levee ridges formed during fluctuating precipitation conditions of the Holocene, when the Pantanal emerged from deglacial aridity. Modern lobes form under heavy seasonal flooding and deposition occurs in response to very rapid and common avulsion events. These results have implications for interpreting
Keywords: Fluvial megafan; Channel patterns; Avulsion Distributary systems; Channel-levees; Pantanal wetland